Effect Of Administration Of Humic Acid On Seed Growth In Varieties Of Cabbage Chili (Capsicum Frutescens L.) At The Seedling Phase - Hibatullah Amtsalul Fatah; Widowati Widowati; I Made Indra Agastya; Roni Syaputra (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This research aims to determine cayenne pepper varieties that produce the best seed growth when applied with humic acid and biochar. Method: This research was carried out at the Malang Regency Sweetener and Fiber Crop Instrument Standard Testing Center which was carried out in June-July 2024. This research used a Randomized Block Design with six treatments and four replications including (P1) = 0 ml humic acid + 0% biochar on crv 212 variety. (P2) = 0 ml humic acid + 0% biochar in carika variety. (P3) = Humic acid 0 ml + biochar 0% in the white gatra variety. (P4) = 6 ml humic acid + 10% biochar on the crv 212 variety. (P5) = 6 ml humic acid + 10% biochar on the carika variety. (P6) = Humic acid 6 ml + 10% biochar in the white gatra variety. Results: The results of this study showed that treatment (P3) = 0 ml humic acid + 0% biochar on the white gatra variety gave the best results in terms of plant height, number of leaves, and shoot and total dry weight. Findings: This research found that the provision of humic acid and biochar can increase the pH, C-organic and N-total values ​​in the planting medium. Novelty and Originality: This research discusses the influence of humic acid and biochar on various varieties of cayenne pepper which contributes to more effective breeding techniques. Conclusion: The conclusion of this study shows that P3 treatment provides the best results, with a significant increase in plant growth parameters and plant dry weight. Type of Paper: Empirical Research Paper.